APPLICATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) PRINCIPLES IN BUSINESS PRACTICES IN INDONESIA - Parlindungan Purba; Micael Jeriko Damanik; Dikki Saputra Saragih; Finceria Trikasari Lawolo (Journal of International Islamic Law, Human Right and Public Policy, 2023)
The application of criminal sanctions to the implementation of corporate social responsibility (CSR) is an important issue in company law. There is a lack of harmony between the regulations governing CSR, such as the Monetary Regulations, the Law on Social and Ecological Obligations of Limited Liability Organizations, and the Regulation on Risk-Limited Organizations. Although these guidelines set out social and ecological obligations for organizations, there is a lack of clarity in determining the types of sanctions that can be applied for violations of CSR commitments. The importance of approval of CSR continues to be linked to the quality of CSR practices. As a legal consequence, permits can be used as a tool to enforce CSR commitments. However, the lack of clarity in the approval guidelines causes confusion in the implementation of sanctions, including criminal sanctions. Therefore, it is necessary to consider revisions in the legislation governing CSR to avoid inconsistency and ambiguity in the implementation of CSR sanctions.